The effectiveness of soursop seed (Annona muricata L.) agains Callosobruchus maculatus F. (Coleoptera: Bruchidae) - Rama Ginanjar Gilang; Nenet Susniahti; Danar Dono (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2018)
Callosobruchus maculatus F. (Coleoptera: Bruchidae) one of the main pests that cause damage to mung beans in storage areas. This research was conducted to determine the effective dose from soursop seed (Annona muricata) powder resulting mortality and emphasizing the amount of imago on the first-generation C. Maculatus. This research was conducted at Plant Pest Laboratory, Department of Plant Pests and diseases, Faculty of Agriculture, Universitas Padjadjaran, Jatinangor using experimental method of Complete Random Design (CRD) with 6 treatments and 5 replications. The treatments were tested using 5 doses of A. muricata seed powder with 1 grams, 3 grams, 5 grams, 7 grams, and 9 grams doses, and added with control or without treatment. The results showed that the dose of 5 grams A. muricata seed powder showed the mortality of C. maculatus by 94% at 8 days after infestation, emphasizing the amount of eggs which is placed C. maculatus of mungbean seed 77,64%. Emphasis on the emergence of the first generation of imago in the mung bean seeds is 74.67%. The lowest of loss weight mung beed seed amount 1,33%.Keywords: Annona muricata, Callosobruchus maculatus, Soursop Seed Powder, Mortality